Pola Manajemen Pembiayaan Pendidikan di Madrasah Aliyah dengan Pendekatan POAC: Studi Kualitatif di MA Bina Insani Cisarua - Baehaqi, Riyandi; Arianti, Ipah; Suryadi; Hayati, Fitroh (Idarotuna: Jurnal Manajemen Pendidikan Islam, 2025)
The purpose of this study was to examine the educational financing management patterns at Madrasah Aliyah (MA) Bina Insani Cisarua using the POAC approach, which stands for planning, organizing, implementing, and controlling. To improve one's comprehension of madrasah financial management practices, this study employed a qualitative methodology with a single-case study design. Data collected through observation, documentation, and interviews were then analyzed using the Miles and Huberman model, which includes presentation, drawing conclusions, and data reduction. The results showed that the POAC principle was effectively implemented at MA Bina Insani, but it was not optimal. There was no digital accounting system to support organization, financing lacked sufficient BOS and SPP funds, and control was carried out only through internal audits and monthly evaluations without a technology-based system. These findings imply the need for financial system digitization, active stakeholder engagement, and diversification of funding sources to improve transparency, accountability, and madrasah financial aspiration. This study has weaknesses because it was conducted on a single-case scale and used qualitative methods, which makes the results more difficult to generalize. Nevertheless, this research contributes to the development of Islamic education management theory based on POAC. Furthermore, it can serve as a practical reference for madrasah administrators in optimizing education financing governance in a sustainable, efficient, and effective manner.